Relationship Between Colours and Emotions as Reflected in Children's Drawings - AYDOS, EMİNE HANDE; Özet, Bahar (John Wiley and Sons Ltd, 2025)
Children articulate their emotions and experiences through drawings and the colours they incorporate into them. This study investigated the relationship between preschool children's colour preferences, the emotions those colours elicit, and how they convey their emotions and thoughts through drawings. The participants, comprising 30 children (19 girls and 11 boys) in Istanbul, were prompted to select a colour card that best represented their feelings and draw a visual representation of their current emotions. Most children linked a single emotion to a specific colour, whereas others demonstrated more intricate emotional representations by associating multiple emotions with one colour. Colour-emotion associations were highly individualised, although some general patterns were observed, and this showcased individual variability shaped by experiences, interactions, and environmental influences. Their drawings predominantly portrayed positive emotions related to family interactions, friendships, and pleasurable activities. Negative emotions were associated with loss, separation, or challenges. These results emphasise the importance of integrating art-based activities into early childhood education to support emotional literacy and communication.
Keywords: Art; Children's Drawings; Colour; Emotional Expression; Preschool Children